Critical success factors of budget hotel performance and mediating role of customer satisfaction - Nazari, Narges (2019)
The emergence of the importance of budget hotels, as one of the main parts of SMEs worldwide, including Malaysia, has been paid attention extensively. The identification of critical success factors (CSFs) is essential for the success of this sector. The evolution of changes in hospitality activities, global transition of budget hotels, and customers’ demands, is expected to identify the underlying success factors for budget hotels’ operations and develop new strategies with the emergence of facing new challenges in developing countries such as Malaysia. The purpose of this study is to identify the critical success factors (CSFs) of budget hotels in Malaysia. This study will also examine the mediating role of customer satisfaction in the relationship between the CSFs and hotel performance. Data collection is performed on budget hotel practitioners (N=212) and hotel guests (N=424) through two self-administered questionnaires. Descriptive statistics (i.e., means, standard deviations and correlation coefficients) were used. Confirmatory Factor Analysis (CFA) and Multiple analysis results using the PLS-SEM application are used to test the proposed hypotheses. The CFA results verified, tested and reported the proposed hypotheses and the relationship between the variables in the current study; along with testing construct validity and reliability. In conducting CFA, items with lower factor loadings were removed. To test the hypotheses, a bootstrap procedure was used. The results indicate that five CSFs could predict budget hotels operations. Meanwhile, four CSFs had positive and significant relationships with customer satisfaction. Customer satisfaction had a strong and positive relationship with budget hotel performance. A significant partial mediation on the influence of CSFs on budget hotel operations through customer satisfaction was identified. Customer Service and Technology were identified as two CSFs that influence budget hotel operations, which were simultaneously mediated through customer satisfaction for the performance of hotels in a Malaysia budget sector context. If hotel managers/owners, in the budget sector, can improve their hotels’ services and use Technology in management, this can help them to satisfy their guests and sustain their businesses at the same time. This study contributes towards understanding the dynamic and changing nature of CSFs; especially from a hotel practitioners’ perspective, in the hospitality sector and confirmation of Resource-based and stakeholder theories. This study also highlights the factors that contribute towards managerial and policy-making implementations for improving Malaysian budget hotel performance.